Casting And Evaluation of Properties for an Aluminum Alloy Material and Optimizing the Quality Control Parameters - Djaksimuratov Karamatdin Mustapaevich; Jumabayeva Guljahon Jaqsilikovna; Maulenov Nurlibek Axmet o’g’li; Rametullayeva Mehriban Po’latbek qizi (Zien Journals, 2022)
The rising cost of steel has had a substantial impact on manufacturing costs in the automobile and household industries, making a compelling case for replacing steel with materials that are lightweight and have a high strength-toweight ratio. Aluminum and its alloys have exceptional features such as light weight, wear durability, and corrosion resistance, making them ideal for a wide range of industrial applications. In today's industry, customer perception of quality is critical, especially with the increased competition. The engine industry is an illustration of how customer expectations in terms of quality and cost are rising across the world. Pistons must meet two important material specifications. One is deformation resistance, or strength when subjected to high combustion pressures and cyclic loads. This is necessary to execute at a high compression range without becoming fatigued, maintaining safe working conditions. Another necessity is high-temperature toughness. This is essential to work at high temperatures without creep in locations where there is a lot of flames. At high temperatures, an aluminum metal alloy containing reinforcing particles demonstrates excellent performance. The stir casting procedure was used to create base aluminum metal alloy matrix LM30+1 percent Graphene+0.8 percent Nickel, LM30+1.5 percent Graphene+0.8 percent Nickel, LM30+1 percent Flyash+0.8 percent Nickel, LM30+1.5 percent Flyash+0.8 percent Garnet. This paper compares the mechanical, chemical, and aluminum alloy of the LM series to meet specified quality control parameters, focusing on the results of impact strength, tensile strength, and hardness. Taguchi methods and other optimization approaches are used to discover the optimal sample that is suitable for use.
Keywords: Aluminum; Compositions; Mechanical properties; Automobile